PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN OBJEK WISATA TAMAN KREATIF PUBLIK KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN PROVINSI RIAU - Melani, Nazila Putri; Maemunaty, Titi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the community’s perception of the development of a publik creative park tourism object, Pangkalan Kerinci District Pelalawan Regency Riau Province. There is a process of selection, preparation, and interpretation in perceiving a tourist attraction. The purpose of this study was to determine how well the public’s perception of the development of the Public Creative Park tourism object, Pangkalan Kerinci District Pelalawan Regency Riau Province. This type of research is descriptive research with a quantitative approach, ini which the data collection process is carried out through a questionnaire and distributed to respondents who were selected as research samples. The sampling technique in this study was simple random sampling. The results of this study found that the Public Creative Park tourism object, Pangkalan Kerinci District Pelalawan Regency Riau Province based on indicators was classified as high. The indicators used in this research are selection, preparation and interpretation.Key Words: Community Perception, Tourism Object Development